2023
DOI: 10.3390/diagnostics13020244
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Macular Thickness after Cataract Surgery in Patients with Open Angle Glaucoma

Abstract: Background: The purpose of this study was to examine the changes in IOP, total macular and RNFL, ganglion cell layer (GCL) thickness, and aqueous humour flare in open angle glaucoma (OAG) patients before and 6 months after cataract surgery. Methods: This was a prospective observational case–control age- and gender-matched study. Groups: 40 subjects in a controlled OAG (OAGc) group, 20 subjects in an uncontrolled OAG (OAGu) group, and 60 control group subjects. Examination: complete ophthalmic evaluation, IOP m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…12,14 Furthermore, glaucoma incidence and OCT RNFL abnormality in cataract candidates have been previously established; Pakuliene et al observed that patients with glaucoma undergoing cataract surgery had lower mean OCT RNFL thickness compared with healthy participants. 24 Abdelmassih et al reported that 14.2% of candidates for cataract surgery had abnormal OCT RNFL findings, and interestingly, 30% of those cases had no history of glaucoma and no detected anomaly on fundus examination. 9 In our study, 16.7% of patients were suspected of having glaucoma based on abnormal OCT RNFL findings.…”
Section: Discussionmentioning
confidence: 99%
“…12,14 Furthermore, glaucoma incidence and OCT RNFL abnormality in cataract candidates have been previously established; Pakuliene et al observed that patients with glaucoma undergoing cataract surgery had lower mean OCT RNFL thickness compared with healthy participants. 24 Abdelmassih et al reported that 14.2% of candidates for cataract surgery had abnormal OCT RNFL findings, and interestingly, 30% of those cases had no history of glaucoma and no detected anomaly on fundus examination. 9 In our study, 16.7% of patients were suspected of having glaucoma based on abnormal OCT RNFL findings.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Gudauskiene et al [ 39 ] found that both the SFCT and the foveal retinal thickness (FRT) increased after phacoemulsification in non-glaucomatous eyes, as measured by SS-OCT; however, the study did not establish a direct correlation between the increases in SFCT and FRT. Interestingly, a study by Pakuliene et al [ 44 ] investigated the late or chronic postoperative changes in the macula of non-glaucoma subjects and controlled and uncontrolled open-angle glaucoma patients using SS-OCT, six months after cataract surgery. The results indicated an increase in macular thickness across all groups.…”
Section: Discussionmentioning
confidence: 99%